Perhitungan Premi Risiko pada Data Klaim Asuransi Kendaraan Bermotor PT Asuransi Wahana Tata Cabang Bukittinggi - Rosita, Silvia; Nopri Bima Sakti; Siska Resti (P3M Trisakti School of Insurance (TSI), 2024)
The insured who pays a nominal premium is a profit for the insurance company. Business actors must be prepared to face claims where losses could exceed the amount of premium income. If the amount of claims that the insurance company must pay is less than or comparable to the total amount of net funds available, then the insurance company can be able to exist longer. If the number of claims that the company will pay is less than or comparable to the amount of net funds available, then the insurance company will be able to survive. Losses can occur even though the premium paid by each policyholder has been calculated. This incident was caused by the large number of claims coming in, causing the value of the claims to become quite large. Based on the description above, this research tries to calculate risk premiums based on data on the number of claims and the amount of claims on motor vehicle insurance coverage with All Risk and TLO coverage types. Using Ozgurel's (2005) formulation at the Bukittinggi branch of the Aswata company from 2018 to 2022. This research used quantitative methodology and secondary data from each motor vehicle insurance policy holder. Based on research findings, the All Risk and TLO protection guarantees ensure that, for each protection guarantee in motor vehicle insurance for 2018–2022, the overall risk premium value isnot much higher than the total claim amount.